Climate Change Governance Practices of Non-governmental Organisations in Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
This article examines the climate change governance practices of non-governmental organisations in Bangladesh. Various stakeholders, including government and non-governmental organizations, are working at national, regional and local levels to address climate change issues. NGOs follow climate change governance practices in their works to make better results for the vulnerable people. In this study five criteria namely, accountability, transparency, participation, effectiveness, and resources were considered to assess the climate change governance practices of NGOs. This paper is based on published documents such as journal articles, reports, books etc. as well as key informant interviews of 34 respondents, to analyse climate change governance practices of the selected seven NGOs of Bangladesh. The surveyed NGOs are now operating to tackle challenges connected to climate change. Moreover, they follow governance protocols while working on climate change–related issues. NGOs, via their efforts in addressing climate change, are significantly improving the lives and quality of life of marginalised individuals. Despite various constraints, the successful contribution of NGOs in enhancing climate governance might strengthen the capacity of vulnerable people to combat climate change-induced disasters.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 105-119